TRAINING MANAGERIAL PERSONNEL FOR ECONOMIC ENTITIES: RESULTS AND PROSPECTS OF DEVELOPMENT - Larisa V. Kartashova; Ol'ga V. Tolstyakova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with one of the most important conditions of Russian economy successful development, i. e. training of managerial personnel. To attain this target the Presidential program of managerial personnel training was started in 1997. The Program was designed subject to the State plan of training managerial personnel and based on state financing of intensive training of managerial personnel for business. The authors studied its key goal - shaping managerial potential of the country that could provide development of enterprises in all spheres of Russian economy and Russian regions and identified prospects of further development of the program.